AEROBIC AND RESISTANCE TRAINING WITH NA INDIVIDUAL WITH DIABETES, HYPERTENSION AND OBESITY AS A RESULT OF LIVER TRANSPLANTATION: A STUDY IN SANTA CRUZ DO SUL, RS, BRAZIL. (Fiep Bulletin - online, 2012)
The patients who undergo liver transplantation are not free from acquiring related diseases, such as: infections, bones thinning, high blood pressure, diabetes, high cholesterol besides becoming obese. This work aimed to evaluate if the effects of aerobic and resistance exercises interfere in the reduction of obesity, diabetes and hypertension resulted from liver transplantation by comparing the pre and post-tests. The research subject was a man of 55 years old that prior to the training period had a body mass of 96,7 kg and height of 1,74 m, giving a BMI of 31,94 (kg/m²). He started the training sessions 10 years after having undergone a liver transplant. The methodological approach was characterized as a pre-experimental study. He performed 24 sessions of resistance and aerobic training which lasted around 60 and 80 minutes each, done 2hours and 30minutes after feeding. For data collection a functional assessment was done, one before and one after the training; analysis of copies of clinical examinations the individual already had and the ones made after the sessions. It was used a blood glucose meter and a digital wrist blood pressure monitor. The general results obtained showed an improvement in the BMI, in the VO2max and the HDL-C, however, with a small increase in total cholesterol and triglycerides. The patient also had a reduction in the WHR from 0,977 to 0,962. Regarding the diabetes, He managed to reduce the daily application of insulin from 20ml to 6ml, keeping the daily GI controlled, having a bigger reduction in the GI laboratory exam. The blood pressure reduced to normal levels.
Keywords: liver transplant; physical exercises; diabetes